PROSPECTS FOR THE USE OF GREEN BONDS IN THE NATIONAL ECONOMY - Rakhmedova Madinakhon Nusrat qizi (Zeta Repository, 2023)
At present, the state of the world economy is characterized by deep contradiction. On the one hand, the issue of transition to a green economy is still on the agenda against the backdrop of aggravated climate risks, on the other hand, in a crisis situation, countries need, if not to achieve sub-standard economic growth rates, then at least to minimize the loss of gross domestic product. Commodity inflation driven by the post-pandemic recovery of economies amid disrupted supply chains, as well as the current political environment, has led to a reprioritization by many green economies and decarbonization advocates. The energy crisis has put states before a choice between energy security and climate risks and, perhaps, only actualized the problem of the transition of developed countries to alternative, green, energy sources. At the same time, to achieve the green goals set by the Paris Agreement, it is necessary to attract a huge amount of investment, which only the financial sector can handle. For example, to achieve carbon neutrality, China will need from 140 to several hundred thousand trillion yuan, and Europe will need investments in the amount of 1 billion euros per year. The uniqueness of green finance as an element of greening the economy is that it can help reduce the degree of climate risks and has an impact not only on the financial sector, but on the entire economy as a whole. That is why the issue of developing green finance is very acute for developed and developing countries.